Are Stock Market Training Programs worth it? - Manda, Vijaya Kittu (SAINTIS Publishing, 2022)
Personal Finance, Investing, and Trading are life skills that prepare individuals to become financially comfortable in their lives and lead happy life. While some of these skills can be acquired from family members or can be drawn from first-hand personal experiences, training programs are found to make a profound positive impact. A questionnaire is administered to 278 stock market participants to understand the impact of stock market training programs conducted in the form of seminars and webinars. The study finds that the training programs have given substantial edge in their trading and investing activities and are worth spending time and money on them. Self-experiences, training programs, and stock market books are the most significant sources of stock market wisdom. Findings from this research can help financial intermediaries in better building investor awareness programs.